Profitability performance under capital structure and other company characteristics : an empirical study of Croatian hotel industry - Karanović, Goran, ekonomist (Array, 2020)
The main objective of this paper is to explore how capital structure and other financial characteristics of companies influence Croatian hotel industry performance. This study’s key goal is to analyze the debt-equity structure of hotel industry and to demonstrate its correlation with financial performance. The high significance and impact of hotel industry on the economy in Croatia was main reason why authors opted to investigate it. This study was carried out using panel data methodology on a sample of 19 Croatian hotel companies listed on the Zagreb Stock Exchange during the period of 2003-2017. Return on assets and return on equity were used as performance proxies and dependent variables. Twelve variables as capital structure measures and other company characteristics – cash ratio, current liquidity ratio, structure ratio, debt ratio, debt factor (in years), equity to non-current assets, total assets turnover, current assets turnover, accounts receivables, activity ratio, return on revenue and crises during the 2009-2015 period – were used as independent variables. The findings suggest that cash ratio, structure ratio, debt factor (in years), equity to non-current assets, total assets turnover, activity ratio, accounts receivables, return on revenue and crises in the 2009-2015 period are related to the financial performance of the Croatian hotel industry. Although profitability performance theory and influence of capital structure and other company characteristic on it is widely studied in financial literature, there are not many studies examining the hotel industry, especially in Croatia. Finally, this study should provide managers with additional insights in making optimal financial decisions.